Effect of statin add-on therapy on cardiovascular mortality - John R. Nelson; Viet Le; Viet Le; Jeffrey L. Anderson; Nicole Ciffone (Frontiers in Cardiovascular Medicine, 2024)
IntroductionCardiovascular (CV) disease remains a leading cause of mortality despite statin therapy. Statin add-on lipid-lowering therapies have been investigated for CV risk reduction, but their effect on CV mortality has not been reviewed.MethodsThis review describes CV outcomes trials of add-on therapies to statins, highlighting findings related to the primary composite CV endpoints and the more patient-centric endpoint of CV-related mortality.ResultsAdd-on ezetimibe met its primary composite CV endpoint vs. statin alone (P = 0.016); however, the individual endpoint of death from CV causes did not differ between groups. Add-on therapy with proprotein convertase subtilisin/kexin type 9 inhibitors achieved the primary composite CV endpoints in the respective CV outcomes trials for alirocumab (P < 0.001) and evolocumab (P < 0.001); however, neither CV outcomes trial found a difference vs. placebo in CV-related mortality. In its CV outcomes trial, icosapent ethyl added to statin therapy significantly reduced the occurrence of the primary composite CV endpoint (P < 0.001) and the individual endpoint of risk of CV-related death (P = 0.03) vs. placebo. A CV outcomes trial of bempedoic acid monotherapy achieved its primary composite CV endpoint vs. placebo (P = 0.004) but not the endpoint of death from CV causes.DiscussionStatin add-on therapies achieved their CV outcomes trial composite CV endpoints. Proprotein convertase subtilisin/kexin type 9 inhibitors and icosapent ethyl have approved indications for CV risk reduction. Only add-on therapy with icosapent ethyl demonstrated a significant reduction in CV mortality in the overall intent-to-treat population, possibly due to the unique pleiotropic mechanisms of eicosapentaenoic acid independent of lipid-lowering effects.